The white darkness : a novel - McCaughrean, Geraldine (New York, NY : HarperTeen, 2009)
Taken to Antarctica by the man she thinks of as her uncle for what she believes to be a vacation, Symone--a troubled fourteen year old--discovers that he is dangerously obsessed with seeking Symme's Hole, an opening that supposedly leads into the center of a hollow Earth.
Includes "extras" about writing and an interview with the author.
Originally published: [Oxford] : Oxford University Press, 2005.
Michael L. Printz Award for excellence in young adult literature from the American Library Association.
Keywords: Deception -- Fiction; Survival -- Fiction; Antarctica -- Fiction; Deception -- Juvenile fiction; Shipwreck survival -- Juvenile fiction; Printz Medal; Antarctica -- Juvenile fiction